Purchase order for supply & installation of zone control assemblies, pipe and other accessories for fire protection system for BRACU new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Signal Technology & Engineering Limited for supply & installation of zone control assemblies, pipe and other accessories for fire protection system for BRACU new campus project.